Effect of storage conditions on sachet water quality in Accra, Ghana - Anna Monney Hammond; Boniface Yeboah Antwi; Elizabeth Von-Kiti; Theophilus Yaw Amponsah; Bosompemaa Gyamera; Eunice A. Ansong (Discover Water)
Abstract Packaged sachet water is a major drinking water source for most low and middle-income classes in sub-Saharan Africa, including Ghana. It has successfully bridged the gap in the supply of safe drinking water to households, supplementing government efforts. However, storage duration and conditions can affect the water quality that reaches consumers. This study examines how storage time and conditions impact the quality of vended sachet water in Accra. Samples were stored using two methods: at room temperature (+ 20 °C) and exposed to sunlight outdoors (+ 33 °C). Water samples were analyzed over 3 months. The average pH of the samples was 7.43 ± 0.23, and all the physicochemical parameters were within World Health Organization guidelines. Some water samples showed bacterial growth after packaging. At 1 month, sachet water B (SWB_Exposed) had a Total Coliform (TC) count of 93 CFU/mL and a Heterotrophic Bacteria count of 416 CFU/mL. By 3 months, all samples contained TC. SWA_Unexposed had a TC of 884 CFU/mL, while SWA_Exposed had 468 CFU/mL. SWB_Unexposed had a TC of 25 CFU/mL, compared to 256 CFU/mL for SWB_Exposed. Currently, sachet water in Ghana has a 3-month expiry date. However, the results suggest that long-term indoor storage of sachet water can lead to bacterial regrowth.